Revisiting the Democracy– Economic Growth Nexus: A Spatial Perspective - Novita Rinusara (Indonesian Journal of Islamic Economics and Finance, 2026)
Regional economy is influenced not only by local factors but also by neighboring factors. This study examines the effect of the Indonesia Democracy Index (IDI) on Provincial Gross Regional Domestic Products (GRDP) in Indonesia from 2016 to 2023. Using both Ordinary Least Square (OLS) and the Spatial Error Model (SEM), this study is one step forward to understanding in ordinary and spatial approach. This study has Average Years of School, Life Expectancy, Domestic Investment, Foreign Investment, Length of Road, and Population Density as control variables, the analysis finds that democracy has a statistically significant negative effect on the provincial economy. But most of the previous studies found the opposite, democracy has a positive effect on the economy. Additionally, the increasing Moran’s I values for IDI indicate a growing level of spatial dependence over time analysis. These findings highlight the importance of incorporating spatial dynamics into economic analysis, as unobserved factors associated with democratic conditions appear to be spatially correlated.